MANAGING ZAKAT IN THE 4.0 ERA: AN IMPLEMENTATION OF SiMBA IN BAZNAS OF NORTH SULAWESI - Nur Fitry Latief (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2019)
SiMBA is a system that was built and developed for the purposes to store data and information owned by Indonesia Zakat Board (BAZNAS) nationally. This study aims to determine the implementation of SiMBA in BAZNAS of North Sulawesi Province and uses a Participatory Action Research (PAR) approach with data collection methods through interviews and observations. The informants consisted of 5 key informants, namely the SiMBA admin and 5 ordinary informants. Data analysis begins with the process of editing, classification, verification, analysis, and formulating conclusions. The results showed that SiMBA has been implemented by BAZNAS of North Sulawesi Province since 2018 which aims to support service performance, accountability in the management of zakat and increase the trust in Muzaki and zakat potential in each region. The application of SiMBA in North Sulawesi Province BAZNAS has been going well and is effective and efficient. SiMBA Admin is divided into two based on their duties, namely the executive admin of the collection field and the admin of the distribution department. Each admin has duties by his field and through this SiMBA the function of control and supervision is carried out very well name in the division of tasks that cannot be accessed by the admin or other parties other than by the executive admin in the field itself. SiMBA also facilitates the presentation of financial reports of all zakat management activities which are transparently and accountably provided to stakeholders and local governments as a form.==============================================================================================Mengelola Zakat di Era 4.0: Implementasi SiMBA pada BAZNAS Sulawesi Utara. SiMBA adalah sistem yang dibangun dan dikembangkan untuk keperluan menyimpan data dan informasi secara nasional yang dimiliki BAZNAS. Penelitian ini bertujuan untuk memastikan proses implementasi SiMBA di BAZNAS Provinsi Sulawesi Utara dan menggunakan pendekatan Participatory Action Research (PAR) dengan metode pengumpulan data melalui wawancara dan observasi. Informan terdiri dari 5 informan kunci, yaitu admin SiMBA dan 5 informan biasa. Analisis data dimulai dengan proses pengeditan, klasifikasi, verifikasi, analisis, dan merumuskan kesimpulan. Hasil penelitian menunjukkan bahwa SiMBA telah dilaksanakan oleh BAZNAS Provinsi Sulawesi Utara sejak 2018 yang bertujuan untuk mendukung kinerja layanan, akuntabilitas dalam pengelolaan zakat dan meningkatkan kepercayaan pada Muzaki dan potensi zakat di setiap daerah. Aplikasi SiMBA pada BAZNAS Provinsi Sulawesi Utara telah berjalan dengan secara efektif serta efisien. Admin SiMBA dibagi menjadi dua berdasarkan tugas mereka, yaitu admin eksekutif bidang pengumpulan dan admin departemen distribusi. Setiap admin memiliki tugas di bidangnya dan melalui SiMBA ini fungsi kontrol dan pengawasan dilakukan dengan sangat baik dalam pembagian tugas yang tidak dapat diakses oleh admin atau pihak lain selain oleh admin eksekutif di bidang itu sendiri. SiMBA juga memfasilitasi penyajian laporan keuangan semua kegiatan pengelolaan zakat yang diberikan secara transparan dan akuntabel kepada para pemangku kepentingan dan pemerintah daerah.